Bifurcations in a Nonlinear Dynamical Model between Western Pacific Subtropical High Ridge Line Index and Its Summer Monsoon Impact Factors. (14th April 2014) - Hong, Mei; Zhang, Ren; Qian, Longxia; Ge, Jingjing; Chen, Jian
Abstract : The western Pacific subtropical high (WPSH) is closely related to Asian climate. Previous studies have shown that a precise dynamical model focusing on the interaction between WPSH and other summer monsoon factors has not been developed. Based on the concept of dynamical model reconstruction, this paper reconstructs a nonlinear dynamical model of subtropical high ridge line (SHRL) and summer monsoon factors from recent 20 years data. Then, using genetic algorithm (GA), model inversion and model parameter optimization are carried out. Based on the reconstructed dynamical model, dynamical characteristics of SHRL are analyzed and an aberrance mechanism is developed, in which the external forcings resulting in the WPSH anomalies are explored. Results show that the configuration and diversification of the SHRL equilibriums have better represented the abnormal activities of the SHRL in short and medium term. Change of SHRL brought by the combination of equilibriums is more complex than that brought by mutation. The mutation behavior from high-value to low-value equilibriums of the SHRL in summer corresponds with the southward drop of the SHRL. The combination behavior of the two steady equilibriums corresponds with disappearance of the "double-ridge" phenomenon of WPSH. Dynamical mechanisms of these phenomena are explained.